Secular trends in the incidence of hip and other osteoporotic fractures. - Cooper, C; Cole, Z; Holroyd, C; Earl, S; Harvey, N; Dennison, E; Melton, L; Cummings, SR; Kanis, J (2011)
Osteoporosis constitutes a major public health problem through its association with age-related fractures, most notably those of the proximal femur. Substantial geographic variation has been noted in the incidence of hip fracture throughout the world, and estimates of recent incidence trends have varied widely. Studies in the published literature have reported an increase, plateau, and decrease in age-adjusted incidence rates for hip fracture among both men and women. Accurate characterisation of these temporal trends is important in predicting the health care burden attributable to hip fracture in future decades. We therefore conducted a review of studies worldwide, addressing secular trends in the incidence of hip and other fractures. Studies in western populations, whether in North America, Europe or Oceania, have generally reported increases in hip fracture incidence through the second half of the last century, but those continuing to follow trends over the last two decades have found that rates stabilise with age-adjusted decreases being observed in certain centres. In contrast, some studies suggest that the rate is rising in Asia. This synthesis of temporal trends in the published literature will provide an important resource for preventing fractures. Understanding the reasons for the recent declines in rates of hip fracture may help understand ways to reduce rates of hip fracture worldwide.